1997
DOI: 10.1177/000456329703400308
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simvastatin Therapy on Cell Membrane Cholesterol Content and Membrane Function as Assessed by Polymorphonuclear Cell NADPH Oxidase Activity

Abstract: SUMMARY. Cell membrane cholesterol is an important determinant of membrane fluidity. Changes in fluidity have important consequences for membrane function. Treatment of hypercholesterolaemia could therefore affect membrane function by reducing cell membrane cholesterol levels. The aim of this study was to determine whether treatment with simvastatin affects membrane cholesterol and the activity of the polymorphonuclear cell membrane enzyme NADPH oxidase. Blood was obtained from 12 hypercholesterolaemic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Bokoch and Prossnitz (1992) showed that lovastatin (0.4-10 µM) decreases formyl-methionyl-leucylphenylalanine-and phorbol ester-induced superoxide radical generation by HL-60 cells (human promyelocytic cell line differentiated to macrophages). A decrease in membrane NAD(P)H oxidase activity of polymorphonuclear leukocytes was observed in hyperlipidemic humans after a 6-week treatment with simvastatin (Day et al 1997). Shishehbor et al (2003b) demonstrated that atorvastatin (10 mg/day for 12 weeks) decreases serum levels of chlorotyrosine and dityrosine that are formed specifically in a myeloperoxidase-dependent manner, suggesting that statin treatment reduces ROS generation by myeloperoxidasecontaining inflammatory cells.…”
Section: Effect On Inflammatory Cellsmentioning
confidence: 98%
“…Bokoch and Prossnitz (1992) showed that lovastatin (0.4-10 µM) decreases formyl-methionyl-leucylphenylalanine-and phorbol ester-induced superoxide radical generation by HL-60 cells (human promyelocytic cell line differentiated to macrophages). A decrease in membrane NAD(P)H oxidase activity of polymorphonuclear leukocytes was observed in hyperlipidemic humans after a 6-week treatment with simvastatin (Day et al 1997). Shishehbor et al (2003b) demonstrated that atorvastatin (10 mg/day for 12 weeks) decreases serum levels of chlorotyrosine and dityrosine that are formed specifically in a myeloperoxidase-dependent manner, suggesting that statin treatment reduces ROS generation by myeloperoxidasecontaining inflammatory cells.…”
Section: Effect On Inflammatory Cellsmentioning
confidence: 98%
“…The ability to scavenge oxygen-derived free radicals is shared by many statins, including simvastatin [141], fluvastatin [142], atorvastatin, pravastatin and cerivastatin [143], and has been demonstrated in a variety of cell types, including macrophages, neutrophils, VSMCs and ECs [141,144]. The functional effects of reduced oxidative stress are varied.…”
Section: Antioxidant Effects Of Statinsmentioning
confidence: 99%
“…In addition to de novo biosynthesis, mammalian cells can take up cholesterol from the extracellular milieu. Exposure to elevated cholesterol levels both in vivo and in vitro enhances cholesterol abundance within the plasma membrane of neutrophils and other blood cells [39][40][41][42]. These findings, in conjunction with the wealth of evidence demonstrating the influence of the extracellular cholesterol levels on neutrophil activity, point to membrane cholesterol enrichment as a potential link between hypercholesterolemia and chronic neutrophil activity.…”
Section: The Influence Of Cholesterol On Neutrophil Activitymentioning
confidence: 77%
“…Lipoproteins (e.g., LDL) in the blood plasma are positioned in close proximity to the circulating blood cells. Conditions that elevate cholesterol-enriched lipoprotein levels may thus favor cholesterol transport into the membranes of these blood cells [39,42]. In the laboratory, cyclodextrin derivatives (e.g., methyl--cyclodextrin or MCD), synthetic cholesterol carrier molecules, are commonly used to alter membrane cholesterol abundance.…”
Section: Transport Of Extracellular Cholesterol Into the Plasma Membranementioning
confidence: 99%